2020
DOI: 10.1590/1807-3107bor-2020.vol34.0007
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine A impairs bone repair in critical defects filled with different osteoconductive bone substitutes

Abstract: The aim of this study was to assess the influence of cyclosporine administration on the repair of critical-sized calvaria defects (CSDs) in rat calvaria filled with diverse biomaterials. Sixty animals were divided into two groups: the control (CTR) group (saline solution) and the cyclosporine (CCP) group (cyclosporine, 10 mg/kg/day). These medications were administered daily by gavage, beginning 15 days before the surgical procedure and lasting until the day the animals were euthanized. A CSD (5 mm Ø) was made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…However, the volumetric reduction of HA/TCP can be around 20% (Favato et al, 2015) without necessarily being associated with the formation of bone tissue (Prisinoto et al, 2020), which may have influenced the smaller volume of mineralized tissues around the implant in the grafted areas with HA/TCP compared with the volume around implants placed in NB observed in this study. In addition, it is likely that the soft tissues constitute a large part of the newly formed tissues in the grafted area (de Coster et al, 2011;Gonçalves et al, 2020), and this may also have influenced the lower degree of osseointegration and biomechanical locking in implants installed in grafted areas with HA/TCP compared to implants installed in NB areas. In fact, previous preclinical and clinical studies have shown that the further away the grafts are from the bone walls, the smaller is the bone formation in the grafted area (Araújo & Lindhe, 2009;de Coster et al, 2011;Pignaton et al, 2020;Prisinoto et al, 2020) the experimental model used in this study, the implants were installed in the middle of the bone defect, which would be the most critical area for bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the volumetric reduction of HA/TCP can be around 20% (Favato et al, 2015) without necessarily being associated with the formation of bone tissue (Prisinoto et al, 2020), which may have influenced the smaller volume of mineralized tissues around the implant in the grafted areas with HA/TCP compared with the volume around implants placed in NB observed in this study. In addition, it is likely that the soft tissues constitute a large part of the newly formed tissues in the grafted area (de Coster et al, 2011;Gonçalves et al, 2020), and this may also have influenced the lower degree of osseointegration and biomechanical locking in implants installed in grafted areas with HA/TCP compared to implants installed in NB areas. In fact, previous preclinical and clinical studies have shown that the further away the grafts are from the bone walls, the smaller is the bone formation in the grafted area (Araújo & Lindhe, 2009;de Coster et al, 2011;Pignaton et al, 2020;Prisinoto et al, 2020) the experimental model used in this study, the implants were installed in the middle of the bone defect, which would be the most critical area for bone formation.…”
Section: Discussionmentioning
confidence: 99%